Mycorrhizal Application and Dosage Material Organic Towards Increasing Chili Pepper Production (Capsicum frutescens) on Goal Plant Cocoa - Mizan Maulana; Suswati; Zulheri Noer; Syafruddin (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Cayenne pepper is a horticultural commodity with high economic value and is widely cultivated by farmers across various regions in Indonesia. In addition to household consumption, cayenne pepper serves as a raw material for the food and beverage industry. Its nutritional content, including vitamin C, vitamin A, lycopene, and various antioxidants, makes this plant important from both health and economic perspectives. However, productivity at the farmer level faces several challenges, including limited use of fertilizers and sustainable organic materials. Excessive reliance on chemical fertilizers can degrade soil fertility and harm the environment. Therefore, the use of organic materials, such as liquid organic fertilizer (POC), and growth-promoting fungi, such as mycorrhizae, offers an environmentally friendly alternative with the potential to increase crop production. This study aimed to determine the effects of different types of organic fertilizers used by farmers, specifically mycorrhizae and POC, and their interactions on cayenne pepper production. The experiment employed a 4 × 3 factorial randomized block design (RBD) with three replications, yielding 12 treatment combinations across two factors. The results showed that mycorrhizae had a significant effect on plant height at 15, 30, and 45 days after planting (DAP), as well as on fresh weight at 110 DAP, but no significant effect on other parameters. Additionally, there was no significant interaction between mycorrhizae and POC doses on any observed parameters. Among the mycorrhizal types tested, Glomus mosseae consistently produced better results compared to other mycorrhizal types throughout the observation period on cayenne pepper plants.